Cases of Lungworm in Cats from Southern Poland in the Autopsy and Cytological Material - Stanisław Dzimira; Małgorzata Kandefer-Gola; Rafał Ciaputa; Marta Demkowska-Kutrzepa (Pathogens)
Lungworms in carnivorous domestic animals are infestations that are relatively uncommon. However, in felines, especially wild ones, they are not at all rare. This study aimed to assess the prevalence of respiratory parasite infections (lung nematodes) in domestic cats based on necropsy and cytological examinations and to highlight the cytological examination of respiratory material as a practical and straightforward diagnostic method. For the presence of lung parasites, necropsy material (cadavers of cats) and samples submitted for cytological examinations from 2005 to 2022 were analyzed. In total, 730 cat samples from southern and southwestern Poland were examined—420 autopsied and 310 cats whose samples were examined cytologically. The material was collected using the bronchoalveolar lavage (BAL) and submitted for cytological examination. Out of 420 cat autopsies, larvae and eggs of Aelurostrongylus abstrusus were found in 4 individuals (0.95%). In cytological material obtained from BAL, out of 310 samples analyzed, larvae and eggs of A. abstrusus and Capillaria aerophila were found in only 2 cases (0.64%). Respiratory parasitic infections in cats can pose a serious health risk, especially with high intensity, in young animals. Considering that such cases present a diagnostic challenge, it is advisable to encourage cat owners to limit their pets’ contact with intermediate and paratenic hosts and use anthelmintics to combat lung parasites.